Why 200°C is Effective for Creating Carbon from Organic Waste (from Thermal Gravity (TG-DTA) Perspective)? - Ragadhita, Risti; Nandiyanto, Asep Bayu Dani (Bumi Publikasi Nusantara, 2023)
The purpose of this study was to evaluate the decomposition of organic waste into carbon microparticles under atmospheric conditions. Carbon microparticles are made by drying and carbonizing raw water hyacinth. Then, the carbon microparticles that have been produced are ground using a saw-milling apparatus. Carbon microparticles prepared from raw water hyacinth were heated in an electric heating furnace at a specific temperature for the analysis. The experimental results show that the thermal decomposition process has three steps. Water hyacinth is stable at temperatures below 100°C. As carbon decomposes at higher temperatures, the process of decomposition into smaller molecules occurs. Then, at temperatures ranging from 150 to 280°C, an effective carbonization process occurs to form carbon. The advantages gained, in this case, will provide a better understanding of how to use heat treatment on water hyacinth.